MORPHO-FUNCTIONAL CHANGES OF HEART AND ADRENAL GLANDS ENDOCRINE SYSTEM UNDER THE INFLUENCE OF COLD FACTOR - Левицький, В. А.; Жураківська, О. Я.; Князевич–Чорна, Т. В. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
This work is dedicated to morphofunctional change research endocrinocytes of adrenal glands and heart at the peak action of general deep hypothermia. It has been established that the most vivid changes occur in the cells of fasciculate zone of cortex and epinephrocytes of medullar substance of adrenal glands. Cold impact, intensive exit of catecholamines and glucocorticoids lead to reactive changes in myoendocrine heart cells with grow of their secretory activity and increasement of auricular sodium-urethic factor exit into blood.